Performance evaluation of a rotary dehumidifier with molecular sieve desiccant using coupled regeneration mode: Experimental investigation - Hussam Bin Mehare; Taliv Hussain; Mohd Aqib Zia; Saif Saleem (Energy and Built Environment)
The increasing demand for energy-efficient and environmentally friendly air conditioning systems has led to the development of innovative technologies such as desiccant cooling systems. This study presents a comprehensive experimental analysis of the dehumidification and thermal performance of a rotary dehumidifier with molecular sieve desiccant designed to effectively remove moisture from the air by utilizing coupled regeneration mode (complete waste heat liberated out of condenser and electric rod heat). Various experiments were conducted to investigate different performance parameters including moisture removed from air by adsorption, moisture added to air by regeneration, dehumidification effectiveness, regeneration effectiveness, moisture removal capacity (MRC), regeneration rate (RR) at different process air inlet temperatures ranging (28–34 °C) and at different regeneration air inlet temperatures ranging (55–62 °C). These experiments were conducted at same air velocity for both adsorption and regeneration segments of rotary solid desiccant wheel using molecular sieve. The results showed that the performance of the desiccant wheel was affected by inlet temperature and humidity ratio for adsorption and regeneration segments. The findings emphasize the system's ability to provide efficient dehumidification and cooling while simultaneously promoting sustainable energy practices. Moreover, the waste heat recovery system significantly contributes to the overall efficiency improvement of the rotary dehumidifier with molecular sieve desiccant, making it an environmentally friendly alternative to conventional air conditioning technologies.